Electron microscopy of model systems - Muller-Reichert, Thomas , 1962- (Methods in cell biology, 2010)
A compendium covering the various aspects of sample preparation of diverse biological systems. It also covers the preparation and analysis of model systems for biological electron microscopy. It includes the most popular systems but also organisms that are less frequently used in cell biology